2001
DOI: 10.1108/02644400110387163
|View full text |Cite
|
Sign up to set email alerts
|

Computational modelling of viscoplastic fluids based on a stabilised finite element method

Abstract: This work is concerned with computational modelling of viscoplastic fluids. The flows considered are assumed to be incompressible, while the viscoplastic laws are obtained by incorporating a yield stress below which the fluid is assumed to remain non‐deformable. The Bingham fluid is chosen as a model problem and is considered in detail in the text. The finite element formulation adopted in this work is based on a version of the stabilised finite element method, known as the Galerkin/least‐squares method, origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
0
17
0
5
Order By: Relevance
“…Such techniques have become standard in Eulerian finite element formulations and have been applied to various problems arising in fluid mechanics (see e.g. [4][5][6][7][16][17][18][19][20][21]). A review of a variety of stabilisation techniques may be found in [22].…”
Section: Discretisation Of the Fluid Flowmentioning
confidence: 99%
“…Such techniques have become standard in Eulerian finite element formulations and have been applied to various problems arising in fluid mechanics (see e.g. [4][5][6][7][16][17][18][19][20][21]). A review of a variety of stabilisation techniques may be found in [22].…”
Section: Discretisation Of the Fluid Flowmentioning
confidence: 99%
“…Pressure can rise to infinity at large volumetric strain ε v = ρ0 ρ − 1 ensured by the state equation p = −K ln (1 − ε v ), in terms of bulk modulus K. The flow characteristics of the granular material is modelled by a Bingham fluid [1,6]. Hence the deviator stress is given by…”
Section: Governing Equationsmentioning
confidence: 99%
“…An linear elastic material behaviour is assumed, which is described by the second Piola-Kirchhoff stress tensor S, the Green-Lagrangian strain tensor and the tensor C of elasticity. C is deduced from the strain-energy function Ψ of the St. Venant-Kirchhoff modelThe motion of viscous and compressible fluids is governed by the Navier-Stokes equations ∂ρv ∂tPressure can rise to infinity at large volumetric strain ε v = ρ0 ρ − 1 ensured by the state equation p = −K ln (1 − ε v ), in terms of bulk modulus K. The flow characteristics of the granular material is modelled by a Bingham fluid [1,6]. Hence the deviator stress is given by…”
mentioning
confidence: 99%
“…Such techniques have become standard in Eulerian ÿnite element formulations for various problems arising in uid mechanics (see e.g. Reference [7]). A review of a variety of stabilization techniques may be found in Reference [8].…”
Section: Introductionmentioning
confidence: 99%